Pengaruh Kualitas Informasi Keuangan Terhadap Kinerja UMKM Di Kota Bandar Lampung - Nurhayati Widi Utami; Sudrajat Sudrajat; Mega Metalia; Agus Zahron Idris (Jurnal Mutiara Ilmu Akuntansi, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are a crucial sector in economic growth. However, they often face challenges in financial management, including accurate and reliable financial reporting. Based on a research activity, it was found that a significant portion of MSMEs do not regularly manage and present financial information. This is attributed to several issues encountered by MSMEs. The main identified problem is the limitation of competent human resources. Most MSMEs lack adequate financial experts. Additionally, some MSMEs face issues such as a lack of understanding of proper financial recording for informed business decision-making. Constraints in time and knowledge of financial management also hinder effective financial information management. This research was conducted on MSMEs located in Bandar Lampung. The sampling technique employed was purposive sampling, in which the researcher specified certain criteria to filter an appropriate sample size deemed relevant to the research objectives. A questionnaire was utilized as a research tool, employing the Structural Equation Model (SEM) for data analysis, including outer model and inner model testing. The research findings indicate that the quality of financial information positively influences the performance of MSMEs in Bandar Lampung.